Gestão de materiais em uma instituição pública do estado do Amazonas - Sousa, André Rebelo (Brasil, 2024)
This study aimed to analyze materials management in a public institution in the state of Amazonas. Data collection was carried out through unstructured interviews with four employees of the institution's Materials Sector, complemented by the observation method. The results highlight the relevance of an integrated annual planning between the materials sector and the general secretariat to map the demands of all sectors, prioritizing the allocation of essential resources. However, technological limitations of the inventory management software, named AJURI, together with insufficient communication between sectors, generate challenges in inventory control, resulting in shortages, especially of essential items, such as food materials. To improve the use of resources, the sector adopts practices similar to the Just in Time (JIT) method, making frequent purchases in small batches, and the XYZ classification, identifying the criticality of materials for the institution, which assist in organizing and prioritizing items according to their criticality and demand. However, the absence of a more modern system and faulty communication hinder the agility and accuracy of stock replenishment, compromising the ability to respond to institutional needs.